The Dynamic Implications of Foreign Aid and Its Variability - Lane, Timothy (IMF Working Papers; Working Paper ;, 2005)
The paper examines the effects of aid and its volatility on consumption, investment, and the structure of production in the context of an intertemporal two-sector general equilibrium model. A permanent flow of aid finances mainly consumption, a result consistent with the historical failure of aid inflows to translate into sustained growth. Shocks to aid are reflected mainly in investment fluctuations, as a result of consumption smoothing. Aid shocks result in substantial welfare losses, suggesting that aid variability should be taken into account in designing aid architecture. These results are consistent with the evidence from cross-country regressions of manufactured exports.